Factors controlling consumer behaviour in frontier towns - KulczyńskaCDFPMR Katarzyna (Bulletin of Geography. Socio-Economic Series)
This article focuses on the most important factors shaping the spatial behaviour of transborder consumers in Słubice and Frankfurt on the Oder, towns split by a state border. The factors are highly diversified and differ in the spatial range of influence. They can be divided into seven groups, viz. geographical, political- administrative, legal-normative, economic, demographic, psycho-social and cultural, and the foreign-language information layout of a town. But it is economic factors, like the level of prices in the given country or the currency exchange rate, that have the strongest effect on the movement of inhabitants and the intensity of transborder contacts between the two frontier towns